1992
DOI: 10.1017/s0079497x0000414x
|View full text |Cite
|
Sign up to set email alerts
|

Excavations in the Neolithic and Bronze Age Complex at Dorchester-on-Thames, Oxfordshire, 1947–1952 and 1981

Abstract: OXI 2EP4 City of Bristol Museum and Art Gallery, Queen's Road, Bristol B S 8 I R L M3 THE PREHISTORIC SOCIETY to the excavation of further surviving parts of the complex: site i, a long D-shaped enclosure incorporated in the southern end of the cursus, and sites 2, 3 and 4.Both sets of sites are presented together, largely following the chronological scheme proposed for the complex by Bradley and Chambers (1988). Site VIII and site 1 are long enclosures of Earlier Neolithic date, with human remains. The lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…Indeed this is in line with the discovery of other major ceremonial complexes from other river valleys in Britain including the Nene (Healy and Harding, 2003;Parry, 2007) and the Thames in Oxfordshire (Whittle et al, 1992). In terms of the fluvial regime a definite increase occurs in lateral reworking of Devensian and presumably earlier Holocene gravels in selected reaches from the early Neolithic onwards.…”
Section: Roadssupporting
confidence: 76%
“…Indeed this is in line with the discovery of other major ceremonial complexes from other river valleys in Britain including the Nene (Healy and Harding, 2003;Parry, 2007) and the Thames in Oxfordshire (Whittle et al, 1992). In terms of the fluvial regime a definite increase occurs in lateral reworking of Devensian and presumably earlier Holocene gravels in selected reaches from the early Neolithic onwards.…”
Section: Roadssupporting
confidence: 76%
“…Despite truncation, a series of mostly single cremation deposits of adults and children were recovered during Ritchie's excavations in the early 1970s, most from standing stone sockets. Balbirnie is part of a much larger complex of monuments which included henge monuments and timber settings at (Willis et al 2016, 353), this is based on an un-tested extrapolation; the largest number of confirmed Middle-Late Neolithic cremation deposits recovered in Britain is actually from Dorchester-onThames, the biggest Neolithic monument complex known to date in the Thames Valley (Atkinson et al 1951;Kinnes 1979;Whittle et al 1992). At Dorchester, a series of monuments associated with the deposition of cremated remains was constructed in the centuries around 3000 cal BC, including multi-phase ring ditches (Site XI), probable timber circles (Sites 3, IV, V & VI), a penannular ring ditch (Site 2), and sites that combined elements of all three enclosure types (Sites I, II & XIV) (see Table 5).…”
Section: Discussion: Cremation Cemeteries In Britainmentioning
confidence: 99%
“…3.3) classified many of these cemeteries as a distinct group in his typological synthesis of round barrows and ring ditches (his Stage E sites). More recent work by Whittle et al (1992) at Dorchester-onThames; Gibson (2010a;Gibson et al 2011) at Duggleby Howe, North Yorkshire and Balbirnie, Fife; Parker- Pearson et al (2009) and Willis et al (2016) at Stonehenge, alongside the new findings at Forteviot, have reasserted the importance of these cemeteries through new fieldwork and analysis.…”
Section: Introductionmentioning
confidence: 95%
“…Some pit circles are enclosed within large ritual areas including some henges (eg, Dorchester XI, Oxfordshire; Atkinson 1951; Whittle et al 1992), to which they may be related (Harding 1987, 26;Kinnes 1979, 67-9;Clare 1986, 287;1987, 459), or ring ditches (eg, Whitton Hill, Northumberland, Miket 1985) whereas others are unenclosed (Barford B, Warwickshire, Oswald et al 1969;Tanat, St. Joseph 1980, 51, fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…However, unabraded sherds from a possible Late Neolithic vessel (fabric 2) were recovered from the grave fill, ditch F216 (Phase 2A) and pit F301 (Phase 2D) which may indicate deposition when these features were open or during backfilling, perhaps suggesting contemporaneity. Ring ditches and pit circles are often found in close association with one another, for example at Dorchester-on-Thames (Atkinson 1951; Whittle et al 1992), Llandegai A (Houlder 1968), and Aldwincle (Jackson 1976).…”
Section: Discussionmentioning
confidence: 99%